2020
DOI: 10.1016/j.isci.2020.101052
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Therapeutic Organoids Using Sacrificial Hydrogels

Abstract: Organoids are becoming widespread in drug-screening technologies but have been used sparingly for cell therapy as current approaches for producing selforganized cell clusters lack scalability or reproducibility in size and cellular organization. We introduce a method of using hydrogels as sacrificial scaffolds, which allow cells to form self-organized clusters followed by gentle release, resulting in highly reproducible multicellular structures on a large scale. We demonstrated this strategy for endothelial ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…In addition to organoids grown in naturally-derived proteins, several laboratories have grown a wide range of organoids in polysaccharides such as alginate or alginate-chitosan mixtures. Organoid types grown in alginate include human lung 99 , 100 , human brain 101 , murine intestinal 102 , human intestinal 102 , 103 , human pancreatic 104 , and human and murine vascular 105 . Capeling and colleagues grew HIOs on an alginate substrate and found that differentiation of human pluripotent cells into HIOs could be supported without the alginate providing chemical cues to the cells.…”
Section: Organoid Culture In Decellularized Ecm and Other Naturally-derived Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to organoids grown in naturally-derived proteins, several laboratories have grown a wide range of organoids in polysaccharides such as alginate or alginate-chitosan mixtures. Organoid types grown in alginate include human lung 99 , 100 , human brain 101 , murine intestinal 102 , human intestinal 102 , 103 , human pancreatic 104 , and human and murine vascular 105 . Capeling and colleagues grew HIOs on an alginate substrate and found that differentiation of human pluripotent cells into HIOs could be supported without the alginate providing chemical cues to the cells.…”
Section: Organoid Culture In Decellularized Ecm and Other Naturally-derived Proteinsmentioning
confidence: 99%
“…The authors hypothesized that cells create their own niche within the alginate hydrogel by secreting basement membrane proteins and forming mesenchyme, allowing cellular survival and differentiation into HIOs 103 . Rossen and colleagues demonstrated the development of murine and human vascular organoids in a non-functionalized alginate setting 105 . Alginate has a number of advantages that make it attractive as a material for further study; it is inexpensive, relatively easy to modify and functionalize, biocompatible, and has been used in a wide range of biological and materials applications 106 108 .…”
Section: Organoid Culture In Decellularized Ecm and Other Naturally-derived Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of xenogeneic contamination and undefined ingredients on the cellular microenvironment and organoid morphology or function remains unclear. To render the induced products amenable to transplantation, organoids need to be fully purified by enzymatic digestion to remove scaffolds (Wang et al, 2017 ; Rossen et al, 2020 ). Another strategy is culture of the organoids in medical grade scaffolds, either derived from decellularized porcine tissues (Giobbe et al, 2019 ) or synthesized with defined components.…”
Section: Remaining Challenges and Prospective Solutionsmentioning
confidence: 99%
“…Last but not least, sacrificial or degradable hydrogels were utilized by Rossen et al to combine cellular clusters with satisfactory reproducibility or scalability, [ 117 ] indicating the importance of hydrogel structure designs. Notably, due to the advantage of 3D unique structure, organoid technology might also be useful for immunology research.…”
Section: Challenge and Opportunities Of Hydrogel‐based Organoids Culturementioning
confidence: 99%